Indigenous Australian Women’s Life Writing: Their Voices to Be Heard - Olga Rorintulus (Journal of International Conference Proceedings (JICP), 2020)
This study argues that Indigenous Australian women’s life writings reveal the empowerment of Indigenous Australian women in terms of expressing their voices and experiences as Indigenous Australian women in Australian society. This study is a qualitative research that collect qualitative data from books and journals through library research. The data are analyzed by applying interdisciplinary approach and presented descriptively. The result of this study shows that Indigenous Australian women’s life writings, If Everyone Care: Autobiography of Margaret Tucker by Margaret Tucker (1977), My Place by Sally Morgan (1987), and Kick the Tin by Doris Kartinyeri (2000) express their political and educative voices in order to enhance their life and potency in Australian society.